A Mn(ii)–MOF with inherent missing metal-ion defects based on an imidazole-tetrazole tripodal ligand and its application in supercapacitors. Issue 35 (25th August 2020) - Wang, Jun; Deng, Shu-Qi; Zhao, Ting-Ting; Zheng, Sheng-Run; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang
Abstract : A 3D Mn(ii )–MOF containing unexpected inherent missing metal-ion defects was constructed, and its application on a supercapacitor was studied. Abstract : A metal–organic framework (MOF), namely SCNU-Z3, based on an imidazole-tetrazole tripodal ligand and Mn(ii ), has been constructed. It exhibits a porous 3D framework composed of truncated octahedron cage subunits. Unexpected ligand-induced missing metal-ion defects were observed in the framework. In addition, the application of SCNU-Z3 in a supercapacitor was performed.